First asymmetric synthesis of the antiepileptic drug lacosamide (Vimpat (R)) based on a hydrolytic kinetic resolution strategy - Muthukrishnan, Murugan; Mujahid, Mohammad; Sasikumar, M.; Mujumdar, P. (Tetrahedron-Asymmetry, 2011)
An efficient asymmetric synthesis of the new antiepileptic drug, Lacosamide is described in high enantiopurity (>98% ee), using Jacobsen's hydrolytic kinetic resolution strategy as a key step. (C) 2011 Elsevier Ltd. All rights reserved.